Impacto da desnutrição infantil na saúde de adultos: revisão de escopo - Pluviose, Windy-Marie Loyola (2023)
Child malnutrition is a nutritional deficiency with multifactorial causes, which is influenced by the social, economic and cultural environment, causing damage to the health of children and adults in different regions of Brazil and in developing and developed countries. Objective: To assess the impact of childhood malnutrition on adult health. Method: This is a scoping review, following the Joanna Briggs Institute (JBI) standard, carried out from February to July 2023. The review was independently performed by three reviewers. From the reading, discussion and observation of disagreement between the results, the inclusion of the studies was carried out based on the consensus among the reviewers. Studies related to child malnutrition that had impacts on adult health were included, analyzed and synthesized in the search, complete texts, without time limitation, in English, Portuguese, Spanish. As for the exclusion criteria, duplicate studies in the same or different databases or data portals were excluded from the search. The review was carried out in the databases: EMBASE, WEB OF SCIENCE, Scopus, BVS and PUBMED. The search generated 6,285 records. After de-duplication and initial screening of titles and abstracts, 104 articles were eligible for full-text review. Of these, 75 studies did not meet the inclusion criteria, which led to a total of 29 studies included in the review. Studies revealed that the impacts of childhood malnutrition on adult health are related to low childhood BMI and high BMI in childhood was associated with an increased risk of outcomes related to Chronic Noncommunicable Diseases (NCDs) in adult life. High levels of childhood malnutrition can result in poor physical growth, recurrent childhood illnesses that further impede development, low cognitive skills and educational attainment, and diminished productivity in adulthood, thus impeding a country's socio-economic development. Child malnutrition is associated with eurodevelopmental problems, academic performance, impaired cognition and behavior, but evidence on possible impacts on mental health is inconclusive. Longitudinal studies have reported later mental health effects with higher levels of depression, anxiety, and low self-esteem in adolescents who were malnourished up to age 2 years compared with non-malnourished; increased depression in adolescents who had severe acute malnutrition in childhood; Increased risk of suicidal ideation and schizophrenia in adults has also been observed. The negative impact of childhood hunger on health across the lifespan into old age has a persistent negative cumulative effect on the quantity and quality of life. Studies have also revealed the risk of obesity in children who experience childhood malnutrition, type 2 diabetes, osteoporosis, heart disease and dementia in old age. Thus, it is concluded that child malnutrition causes serious damage to the health of adults due to the possibility of developing metabolic, cardiac and mental diseases, in addition to economic impacts for the treatment of chronic non-communicable diseases in the country.